Physiotherapy in the management of non-communicable diseases: facing the challenge - J. M. Frantz (AOSIS, 2005)
There is mounting evidence of the rising incidence and prevalence of non-communicable diseases in developing countries. Governments are facing serious challenges in health care due to the rising trends in non-communicable diseases as a result of demographic and epidemiological changes, as well as economic globalization. Cardiovascular disease, cancers, diabetes, respiratory disease, obesity andother non-communicable conditions now account for 59 percent of the 56.5 million global deaths annually, and almost half, or 46 percent, of the global burden of disease. It is estimated that by 2020, non-communicable diseases will account for 60% of the global burden of disease. The burden of non-communicable diseases in sub-Saharan Africa is already substantial, and patients with these conditions make significant demands on health resources. How do these changes affect physiotherapists? This paper aims to highlight the need for physiotherapists to shift their focus from curative to preventive care in order to face the challenge of non-communicable diseases.